The effect of chewing royal gala apples on the formation of plaque and the salivary pH in grade VI students of SDIT assunnah cirebon - Sulistyanti, Aprillia Dini (Journal of Oral Health Care, 2020)
Plaque and salivary pH are factors that can cause dental caries. The prevalence of caries according to RISKESDAS (2018) reached 45.3% in Indonesia. WHO (2012) states that the prevalence of caries for school children at 60%-90%. They are fond of consuming kariogenic foods that can increase the risk of caries. The Royal Gala Apple contains antibacterial that can inhibit plaque formation and have a slight acid flavor that can stimulate saliva flow. Aim: To know the influence of chewing the Royal Gala Apples to plaque formation and salivary pH in grade VI students SDIT Assunnah Cirebon. Method: Quasi experiment with one group pretests posttest design. Samples of 33 students. The samples were instructed to chew the Royal Gala Apple 100 gr for 5 minutes. Plaque measured by PHP index and salivary pH is measured with universal indicator paper. Results: The normality test of Kolmogorov-Smirnov is obtained by the plaque and salivary pH results before and after chewing the Royal Gala p-value of < 0.05 so, that distribution data is abnormal. Data analyzed using Wilcoxon test was obtained PHP plaque index and salivary pH before and after chewing Apple Royal Gala p-value: 0.000 (sig < 0.05) Conclusion: there is a chewing effect of the Royal Gala Apple Fruit against plaque formation and salvary pH in grade VI students SDIT Assunnah Cirebon.